(untitled) (Plant Tissue Culture and Biotechnology, 2025)
A study was conducted to standardize in vitro propagation techniques of mulberry (Morus alba) using nodal segment and shoot tip culture. A high frequency of shooting (80%) from nodal segment and shoot tips (78%) were recorded on MS medium supplemented with various concentration and combination of BAP, Kn and two amino acids (L-asparagine and L-glutamine). BAP (2.0 mg/l) + NAA (0.2 mg/l) in addition with L-asparagine (1.0 mg/l) and L-glutamine (25 mg/l) with MS medium proven to be the best combination for multiple shoot formation in experimental mulberry genotypes. This medium facilitated the elongation of shoots and sprouting of axillary buds of in vitro grown shoots. Best performance was recorded in case of five genotypes viz. China white, BSRM19, BSRM63, BSRM34, and BSRM45 for calli induction and plant regeneration. 100% rooting was found when the medium was fortified half strength of MS + IBA (1.0 mg/l). The plantlets with well-formed root systems were gradually acclimatized in shade house using soil: coco peat (1:1) and finally plants were transferred to the field for further development. Plant Tissue Cult. & Biotech. 34(2): 105-114, 2024 (December)